Optimization of broadband white light continuum in gases for Z-scan and other nonlinear applications (2019)
The supercontinuum (SC) has attracted attention as an ideal tunable ultrafast white-light laser source. Frequency broadening has had a great deal of research interest since its appearance in early 1970's in condensed media. A large number of experiments and new theories have been developed to explain the mechanism of supercontinuum, also called white light continuum (WLC). Supercontinuum generation occurs when narrow-band incident pulses propagate inside a material. In gases, nonlinear effects such as self-focusing and self-phase modulation (SPM) balance with plasma nonlinearities via multi-photon ionization to create a filament. In case of waveguides, the propagation in anomalous regime, gives place to soliton formation. This happen when the phase accumulated by group velocity dispersion (GVD) and phase collected by the Kerr effect compensates each other. High order solitons can break into a series of fundamental solitons due to perturbation over the propagation. This effect is called soliton fission, and it is the main mechanism for supercontinuum generation (SCG) in waveguides. In this dissertation, an explanation of the nonlinear effects involved in WLC generation in gases and waveguides is made as an effort to derive a pulse propagation equation for each case. Our end goal is to use a single high power broadband source that can replace conventional tunable sources of radiation as optical parametric generators/amplifiers (OPGs/OPAs) in Z-scan applications. We show that gases are ideal for higher energy WLC generation due to their higher optical damage threshold than for condensed media. In this dissertation we demonstrate infrared (IR) SCG in a range of 800 - 1600 nm by pumping a Krypton (Kr) gas chamber at 1800 nm. The WLC generated in this work had high enough quality beam pro_les to perform closed and open aperture WLC Z-scans in the infrared from 1000 nm to 1550 nm. Its capability of measuring nonlinear absorption (NLA) and nonlinear refraction (NLR) coeffcients was proven measuring Gallium Arsenide (GaAs), Silicon (Si), and Carbon disulfide (CS2). Nonlinear characterization is important when it is necessary to predict a material behavior for an specific application. As an example, materials with high two photon absorption (2PA) can be used in micro-fabrication applications, optical data storage, bio-imaging and optical power limiting. Materials with high nonlinear refractive index can be used as optical switches or for soliton generation. Techniques such as Z-scan has been used world wide for nonlinear characterization. Thus, we performed conventional Z-scan using a Clark laser and a TOPAS-C to characterize the nonlinear behavior of a thin-film highly-doped semiconductor. Specifically, this Indium Tin oxide (ITO) semiconductor was analyzed at a particular region of wavelength which presents enhanced nonlinearities. The enhancement region turns out to be where the real part of the permittivity becomes zero, hence was denominated epsilon-near-zero (ENZ) region. In particular for ITO, the ENZ wavelength happen at near infrared. This kind of materials have recently become a popular topic because the change in the refractive index is larger than 380 %. Some application was developed in this field, for example, nanoantennas which have a recovery time less than picoseconds, beside of the intensity and wavelength dependence. Another effort of this dissertation is to perform simulation in some applications using nonlinearities in highly nonlinear fibers called photonic crystal fiber (PCF). PCF consist in a narrow core surrounded by a cladding made by large number of air holes. The geometry involved in this type of fibers, can highly confine the light and also the refractive index contrast between the core and cladding enhance the nonlinearities. The purpose of the last chapter of this dissertation is to show SCG after propagation of few centimeters inside a CS2 liquid-core PCF (LCPCF). The CS2-LCPCF is a PCF infiltrated with CS2 as an effort to further enhance the nonlinear properties of the PCFs. Additionally, it is shown a nonlinear switch made by the coupling between two infiltrated holes next to the silica core in a PCF. This at the same time uses less power than conventional switches.